Exciton dipole-dipole interaction in a single coupled-quantum-dot structure via polarized excitation - Kim, H; Kim, I; Kyhm, K; Taylor, R; Kim, J; Song, J; Je, K; Dang, L (American Chemical Society, 2016)
We find that the exciton dipole–dipole interaction in a single laterally coupled GaAs/AlGaAs quantum dot structure can be controlled by the linear polarization of a nonresonant optical excitation. When the excitation intensity is increased with the linearly polarized light parallel to the lateral coupling direction [11̅0], excitons (X1 and X2) and local biexcitons (X1X1 and X2X2) of the two separate quantum dots (QD1 and QD2) show a redshift along with coupled biexcitons (X1X2), while neither coupled biexcitons nor a redshift are observed when the polarization of the exciting beam is perpendicular to the coupling direction. The polarization dependence and the redshift are attributed to an optical nonlinearity in the exciton Förster resonant energy transfer interaction, whereby exciton population transfer between the two quantum dots also becomes significant with increasing excitation intensity. We have further distinguished coupled biexcitons from local biexcitons by their large diamagnetic coefficient.